The Effect of Non-Performing Loans, Loan to Deposit Ratio, and Capital Adequacy Ratio on Profitability in State-Owned Banks for the 2018-2024 Period - Ferdina Watiningsih (Indonesian Journal Economic Review (IJER), 2026)
This study aims to examine the influence of Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Capital Adequacy Ratio (CAR) on profitability measured using Return on Assets (ROA) in state-owned banks listed on the Indonesia Stock Exchange for the 2018–2024 period. The research approach used is quantitative with multiple linear regression analysis methods. The research data is sourced from the annual reports of four state-owned banks, namely PT Bank Rakyat Indonesia Tbk, PT Bank Negara Indonesia Tbk, PT Bank Mandiri Tbk, and PT Bank Tabungan Negara Tbk. The analysis process is carried out through a partial test (t-test), simultaneous test (F-test), and calculation of the determination coefficient (R²). The results of the study revealed that partially, NPL had a significant negative influence on ROA with a regression coefficient value of -0.772 and a significance level of 0.000 < 0.05. The LDR variable did not show a significant effect on ROA with a significance of 0.092 > 0.05, nor did CAR which also had no significant effect with a significance of 0.648 > 0.05. However, simultaneously these three variables were shown to have a significant effect on ROA with F calculated at 19.744 greater than F in table 2.99 and Adjusted R² value of 0.676. This means that 67.6% of ROA variations can be explained by NPLs, LDRs, and CARS, while the remaining 32.4% are influenced by other factors outside of this research model.